Integrasi Nilai-Nilai Ekonomi Islam dalam Pembangunan Ekonomi Nasional: Peluang dan Tantangan di Era Globalisasi - Violin Ladies Aulia (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Globalization brings both opportunities and challenges to national economic development, such as increased integration of global markets, while also triggering economic inequality, financial instability, and the marginalization of social justice values. This condition necessitates an alternative development paradigm that is not solely growth-oriented but also grounded in ethics and social welfare. This study aims to analyze the concepts and forms of integrating Islamic economic values into Indonesia’s national economic development and to identify the opportunities and challenges of their implementation in the era of globalization. The research employs a qualitative descriptive approach using a literature review method. Data were obtained from books, scholarly journal articles, official institutional reports, and academic publications relevant to Islamic economics, national development, and globalization. Data analysis was conducted using qualitative analytical techniques to identify concepts, forms of integration, opportunities, and challenges of Islamic economics in national development. The findings indicate that the integration of Islamic economic values through Islamic financial instruments, optimization of ZISWAF, development of the halal industry, and empowerment of sharia-based MSMEs and pesantren-based economic activities contributes positively to inclusive economic growth and improved social welfare. These instruments play an important role in strengthening income distribution, social stability, and financial inclusion. The study concludes that strengthening Islamic economic literacy, harmonizing regulations, leveraging digital innovation, and fostering multi-stakeholder collaboration are key strategies for optimizing the role of Islamic economics in supporting equitable and sustainable national economic development amid globalization.